Force Majeure for E-commerce Transaction during the Covid-19 Pandemic - Wilma Laura Sahetapy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Covid-19 pandemic has brought major changes to the economic structure. Some changes in the economy appear to be declining in conventional activities, but e-commerce transactions actually show a rising curve during the pandemic. The pandemic makes e-commerce transactions a better option for the community to shop their daily needs, because all people must stay at home. The advantage of e-commerce transactions is the ease of use because all business people turn to this transaction. However, the increase in e-commerce transactions is also followed by numerous problems, such as breaking the agreement made during the e-commerce transaction. This agreement on e-commerce transactions does not provide clauses regarding force majeure. This actually makes consumers feel violated because the actual achievements that must be fulfilled cannot be done because of the condition of this 19th pandemic, such as the delivery limitations that cause delaying or finally cancelling the order by the business people. Force majeure in the Covid-19 pandemic can be categorized as an unexpected event that results in the cancellation of an achievement or delayed achievement. If the agreement made does not contain a force majeure clause, there is no legal force to challenge the default that has been done by the business people. Therefore, it depends on the clause that is included in making the e-commerce transactional agreements.